Myeloid-derived suppressor cells at diagnosis may discriminate between benign and malignant ovarian tumors. Issue 9 (3rd November 2019) - Coosemans, An; Baert, Thaïs; Ceusters, Jolien; Busschaert, Pieter; Landolfo, Chiara; Verschuere, Tina; Van Rompuy, Anne-Sophie; Vanderstichele, Adriaan; Froyman, Wouter; Neven, Patrick; Van Calster, Ben; Vergote, Ignace; et al.
Abstract : Background: The behavior of the immune system as a driver in the progression of ovarian cancer has barely been studied. Our knowledge is mainly limited to the intra-tumoral adaptive immune system. Because of the widespread metastases of ovarian cancer, an assessment of the circulating immune system seems more accurate. To demonstrate the presence of immune cells in blood samples of patients with ovarian neoplasms. Methods: In this exploratory prospective cohort study, peripheral blood mononuclear cells were collected at diagnosis from 143 women, including 62 patients with benign cysts, 13 with borderline tumor, 41 with invasive ovarian cancer, and 27 age-matched healthy controls. Immune profile analyses, based on the presence of CD4 (cluster of differentiation), CD8, natural killer cells, myeloid-derived suppressor cells, and regulatory T cells, were performed by fluorescence activated cell sorting. Results: In a multivariable analysis, six immune cells (activated regulatory T cells, natural killer cells, myeloid-derived suppressor cells, monocytic myeloid-derived suppressor cells, exhausted monocytic myeloid-derived suppressor cells, and total myeloid cells) were selected as independent predictors of malignancy, with an optimism-corrected area under the receiver operating characteristic curve (AUC) of 0.858. In contrast, a profile based on CD8 and regulatory T cells, the current standard in ovarian cancer immunology, resulted in an AUC of 0.639. Conclusions: Our immune profile in blood suggests an involvement of innate immunosuppression driven by myeloid-derived suppressor cells in the development of ovarian cancer. This finding could contribute to clinical management of patients and in selection of immunotherapy.